Preschool-aged children's hair cortisol and parents' behavior, psychopathology, and stress. (May 2023) - Isaac, Akira J.; Rodriguez, Alyssa M.; D'Anna-Hernandez, Kimberly; Gemmell, Natalie; Acedo, Gillian R.; Dougherty, Lea R.; Bufferd, Sara J.
Abstract: Parental factors, including parenting behavior, parent mental health, and parent stress, are associated with child stress. More recently, studies have shown that these parental factors may also be associated with children's hair cortisol concentration (HCC). HCC is a novel biomarker for chronic stress. HCC indexes cumulative cortisol exposure thereby reflecting longer-term stress reactivity. Although HCC is associated with a range of problems in adults such as depression, anxiety, appraisal of stressful events, and diabetes, studies investigating HCC in children have been inconsistent, with particularly little information about parental factors and HCC. As chronic stress may have long-term physiological and emotional effects on children, and parent-based interventions can reduce these effects, it is important to identify parental factors that relate to children's HCC. The aim of this study was to examine associations between preschool-aged children's physiological stress measured via HCC and mother- and father-reported parenting behavior, psychopathology, and stress. Participants included N  = 140 children ages 3–5-years-old and their mothers ( n  = 140) and fathers ( n  = 98). Mothers and fathers completed questionnaire measures on their parenting behavior, depressive and anxiety symptoms, and perceived stress. Children's HCC was assessed by processing small hair samples. HCC levels were higher in boys compared to girls, and higher in children of color compared to white children. There was a significant association between children's HCC and fathers' authoritarian parenting. Children's HCC was positively associated with physical coercion, a specific facet of fathers' authoritarian parenting, even after accounting for sex of the child, race/ethnicity of the child, stressful life events, fathers' depression, fathers' anxiety, and fathers' perceived stress. In addition, there was a significant interaction between higher levels of both mothers' and fathers' authoritarian parenting and children's HCC. Children's HCC was not significantly related to mothers' and fathers' anxiety and depression or mothers' and fathers' perceived stress. These findings contribute to the large literature that links harsh and physical parenting practices with problematic outcomes in children. Highlights: Higher HCC in boys than girls, and children of color compared to white children. Children's HCC was positively associated with fathers' authoritarian parenting. Children's HCC was positively associated with fathers' physical coercion. Interaction between mothers' and fathers' authoritarian parenting and children's HCC. Children's HCC was not linked to parents' anxiety, depression or perceived stress.